DESTINATION OF PUBLIC FORESTS IN BRAZIL: AN ANALYSIS OF FOREST CONCESSIONS (Nativa, 2018)
DESTINO DAS FLORESTAS PÚBLICAS NO BRASIL: ANÁLISE DAS CONCESSÕES FLORESTAIS  The forest concession policy objective is to prevent forest degradation, transfer part of the functions and public responsibilities to the private sector and at the same time increase income and improving the life quality of local people. Of the total 310.7 million hectares of federal public forests in Brazil, 77% are destined areas and 23% hectares of are not destined areas. However, the areas under concessions are the National Forests, a conservation unit with the objective of sustainable multiple use of forest resources and scientific research. In this context, this paper aims to discuss two points related to the forest concession on destined areas, first regarding financial resources for monitoring activities of Public Forests under concessions and for the maintenance of conservation units; and the second regarding the indicators measured in the management area under forest concession.Keywords: destined areas, national forests, national cadastre of public forests. RESUMO:O objetivo da política de concessão florestal é prevenir a degradação das florestas, transferindo parte das funções e responsabilidades públicas para o setor privado e, ao mesmo tempo, aumentar a renda e melhorar a qualidade de vida das pessoas locais. Do total de 310,7 milhões de hectares de florestas públicas federais no Brasil, 77% são áreas destinadas e 23% são áreas não destinadas. No entanto, as áreas sob concessões são as Florestas Nacionais, uma unidade de conservação com o objetivo de uso múltiplo sustentável de recursos florestais e pesquisas científicas. Neste contexto, este artigo tem como objetivo discutir dois pontos relacionados à concessão florestal em áreas destinadas, primeiro em relação aos recursos financeiros gastos para monitorar atividades em Florestas Públicas sob concessões e a manutenção destas mesmas áreas como unidades de conservação; e o segundo relacionado aos indicadores medidos na área de gerenciamento sob concessão florestal.Palavras-chave: áreas destinadas, florestas nacionais, cadastro nacional de florestas públicas. DOI: http://dx.doi.org/10.5935/2318-7670.v05nespa06